Effect of zinc crystals size on galvanized steel deformation and electrochemical behavior - Culcasi, José Daniel (2009)
Hot-dip galvanized steel sheets with different spangle sizes were deformed by means of rolling and tension. The change of preferential crystallographic orientation and of superficial characteristics due to the deformation was analyzed by means of both X-rays diffraction and optical and scanning electronic microscopy. A correlation between such changes and the involving deformation modes was intended to be done and the spangle size influence on these modes was studied. Coating reactivity change due to the deformation was investigated by means of quasi-steady DC electrochemical tests. The results allow to infer that, in great spangle samples, the main deformation mechanism is twinning whereas in small spangle ones, pyramidal slip systems happen as well. The increase of the reactivity with the deformation is greater in tension than in rolling and it is more important in small than in great spangle samples.